2012
DOI: 10.1039/c2cc16072b
|View full text |Cite
|
Sign up to set email alerts
|

The first facile stereoselectivity switch in the polymerization of rac-lactide—from heteroselective to isoselective dialkylgallium alkoxides with the help of N-heterocyclic carbenes

Abstract: The reaction of N-heterocyclic carbene (NHC) with dimeric dialkylgallium alkoxides, acting as nonselective or heteroselective catalysts in the polymerization of rac-LA, leads to highly active and isoselective monomeric Me(2)Ga(NHC)OR catalysts, resulting for the first time in the facile switch of stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 41 publications
7
70
0
1
Order By: Relevance
“…The reaction of 6-enyl-9-aryl-, 6,10-dienyl-13-aryl-, or 6,10,14-trienyl-17-aryl-propargylic silyl ethers in the presence of InI 3 (20 mol%) afforded the corresponding tricyclic, tetracyclic, or pentacyclic allylic silyl ethers (54). 82 The use of InBr 3 and other metal-based Lewis acids led to lower catalytic activity.…”
Section: Cascade Polycyclization Of Polyenyl Propargylic Silyl Ethersmentioning
confidence: 99%
“…The reaction of 6-enyl-9-aryl-, 6,10-dienyl-13-aryl-, or 6,10,14-trienyl-17-aryl-propargylic silyl ethers in the presence of InI 3 (20 mol%) afforded the corresponding tricyclic, tetracyclic, or pentacyclic allylic silyl ethers (54). 82 The use of InBr 3 and other metal-based Lewis acids led to lower catalytic activity.…”
Section: Cascade Polycyclization Of Polyenyl Propargylic Silyl Ethersmentioning
confidence: 99%
“…Previously, we have shown that 1 reacts with weak Bronsted acid CDCl 3 to form (S,S)-[Me 2 Ga(μ-OCH(Me)C(O)OMe)] 2 and SIMesD(CCl 3 ) adducts. 19 Moreover, the equimolar reaction between 1 and Me 3 Ga resulted in the formation of Me 3 Ga(SIMes) and (S,S)- 26g The analogous reaction for 5 allowed for the isolation of Me 3 Ga(IMes) (8) (Scheme 2). The structure of 8 was determined both in the solid state by X-ray analysis ( Figure 7) and in solution, and is discussed later in the text along with the coordination properties of NHC toward akylgallium complexes.…”
Section: ■ Introductionmentioning
confidence: 97%
“…It represents the first example of a facile switch of stereoselectivity in the polymerization of rac-LA. 19 In the above case, Me 2 GaOR-(NHC) complexes were also the very rare example of isoselective catalysts highly active at low temperatures. 7a,20 Therefore, the detailed understanding of the influence of NHCs on the structure and activity of Me 2 GaOR(NHC) should be important for the design of new catalysts based on main group metal alkoxides for the controlled and stereoselective polymerization of PLA and other heterocyclic monomers.…”
Section: ■ Introductionmentioning
confidence: 97%
See 2 more Smart Citations